Measuring market orientation, innovative marketing strategies and performance: evidence from the Malaysian agro-food manufacturers - Kamarulzaman, Nitty Hirawaty; Khairuddin, Nurul Hasyima; Hashim, Haslinda; Hussin, Siti Rahayu (Emerald Publishing, 2021)
Purpose - This paper aims to investigate the relationship between market orientation and innovative marketing strategies and the effect of innovative marketing strategies on the performance of agro-food manufacturers. Design/methodology/approach - Systematic random sampling was used, and semi-structured interviews were conducted with 380 agro-food manufacturers. Several statistical analyses, including Pearson correlation analysis and logistic regression analysis, were used to analyze the relationship between market orientation and innovative marketing strategies, and the effect of innovative marketing strategies on the performance of agro-food manufacturers. Findings - All dimensions of market orientation – customer orientation, competitor orientation and inter-functional coordination – have significant relationships with innovative marketing strategies (product, price, promotion and distribution), while customer orientation and promotion showed a very strong relationship among other variables measured. Innovative marketing strategies, specifically promotion, had the most effect on the performance of agro-food manufacturers. Research limitations/implications - The sample for this study was selected among agro-food manufacturers in major locations in Peninsular Malaysia. Hence, the findings may only give an initial overview of the current state of the agro-food manufacturers. Originality/value - This study highlighted the significance of market orientation and innovative marketing strategies for the betterment of performance in the agro-food manufacturing sector.